Semarang Sues Action: Student Collective Action From a Port City on The North Coast of Java - Muhammad Zulfa Alfaruqy (Green Publisher, 2025)
The budget efficiency policy instructed by the government has triggered a wave of rejection from student elements in various regions of Indonesia, one of which is manifested in the Semarang Sues Action (Aksi Semarang Menggugat). This study aims to understand the motivation and manifestation of college students' collective action in the Semarang Sues Action. This study uses a case study approach and collects data from in-depth interviews with eight participants, participatory observation, and digital documentation. Data analysis was carried out using thematic analysis. The results show that college students in Semarang interpret the budget efficiency policy as a form of government injustice towards the education sector. The perception of this injustice arouses anger, which encourages them to be involved in collective action, both digital activism and demonstrations. Demonstrations delineate actions that completely organized by college student organizations, while digital activism is more fluid and not completely organized by them. College students use both forms of action to express emotions and demand the government to change the policies. This study contributes to political psychology by emphasizing the relationship between identity, perceptions of injustice, and anger in driving college student collective action. In addition, the study highlights the role of college student organizations as pressure groups that drive the mobilization of action, and the role of digital media as a free space that escalates the mobilization of ideas in the digital era.